Efeito da infecção pelo vírus SARS-CoV-2 em biomarcadores metabólicos e sua relação com o Diabetes Mellitus: follow-up de 12 meses - Figueiredo Neta, Joana Furtado de (2023)
The study aimed to investigate changes in metabolic biomarkers in people without diabetes, after SARS-CoV-2 infection over 12 months. It was an epidemiological and longitudinal study, with a quantitative approach, carried out in the Primary Health Centers of the city of Baturité in Ceara, Brazil from October 2021 to November 2023. The study population consisted of adults, over 18 years old, with a positive diagnosis for infection with the SARS-CoV-2 virus. The inclusion criteria adopted were: people of legal age, from both sexes, and with a confirmed diagnosis of Covid-19. The exclusion criteria were: people diagnosed with pre-diabetes or diabetes, using glucocorticoids and/or psychotropic drugs, hospitalized for less than 30 days or presenting complications that could compromise the analysis. Data collection was carried out by applying a form containing sociodemographic, anthropometric, lifestyle, and clinical variables. In addition, four blood samples were collected to evaluate metabolic biomarkers. The following outcome variables were considered: incidence of prediabetes and diabetes. For data analysis, the analysis of variance of the outcomes was estimated separately, then the amount of variance was defined in different scenarios among those who developed diabetes and/or prediabetes . Furthermore, the severity of the disease was considered as mild, moderate and severe to associate the variables. These variables were presented as mean and standard deviation, as median and percentiles, frequency and prevalence rate. The Mann-Whitney U test was used to analyze participant characteristics and the Pearson chi-square test and Fisher's exact test were used for associations between variables. The final sample was made up of 184 people, with the majority being female participants (65%), mixed race (63%), average age of 42 years (SD±13.0), sedentary (65%) and in alcohol consumption (39%). Regarding the severity of the disease, 88.9% had a mild form and 11.5% had moderate/severe conditions. The study demonstrated that, in most blood collections, glycemic, hepatic and renal markers had high averages in moderate/severe cases of Covid-19, showing a significant association. Several biomarkers had sustained elevations during the 12 months of follow-up. The accumulated risk curve demonstrated that, at the end of 12 months, 44.1% and 48.5% of participants were at risk of developing pre-diabetes/diabetes and insulin resistance, respectively. The study presented, at the end of the follow-up, an incidence of 15.1% of people with pre- diabetes and 1.6% with Diabetes Mellitus. In view of this, the importance of long-term monitoring of the population affected by Covid-19 is seen, as the sequelae can affect various functions of the body, leading to persistent metabolic disorders. A more comprehensive investigation of such complications is necessary, through follow-up for a period of more than 12 months due to the lack of knowledge about the concrete consequences resulting from SARS-CoV-2 infection.